Evaluation of Skin Biophysical Parameters and Angiogenesis Using CD34 as a Biomarker in Older Diabetic Women Treated with Radiofrequency - Sobkowska D; Gornowicz-Porowska J; Seraszek-Jaros A; Słomińska D; Adamski Z; Pawlaczyk M (Dove Medical Press, 2022)
Daria Sobkowska,1 Justyna Gornowicz-Porowska,1 Agnieszka Seraszek-Jaros,2 Daria Słomińska,3 Zygmunt Adamski,4 Mariola Pawlaczyk1 1Department and Division of Practical Cosmetology and Prevention of Skin Diseases, Poznan University of Medical Sciences, Poznań, 60-806, Poland; 2Department of Bioinformatics and Computational Biology, Poznan University of Medical Sciences, Poznań, 60-806, Poland; 3Department of Pharmacology, Poznan University of Medical Sciences, Poznan, 60-806, Poland; 4Department of Dermatology, Poznan University of Medical Sciences, Poznan, 60-355, PolandCorrespondence: Daria Sobkowska, Poznan University of Medical Sciences, 3 Rokietnicka Street, Poznań, 60-806, Poland, Tel +48 61 848-04-75, Email daria.sobkowska@gmail.comBackground: The prevalence of type 2 diabetes mellitus (t2DM) has been steadily increasing. Patients with t2DM need to slow down the skin ageing processes and to obtain a rejuvenating effect. Treatments that do not damage the superficial layers of the epidermis could be a promising solution for those patients.Purpose: The aim of this study was to evaluate the effects of radiofrequency therapy on the biophysical parameters and angiogenesis of facial skin, using CD34 as a biomarker in older diabetic women treated with metformin.Patients and Methods: A total of 45 subjects with phototype 2 or 3 (Fitzpatrick scale) were investigated (25 t2DM – study group, 20 – healthy controls). A series of 6 treatments (once a week) with a Radio Frequency Skin Rejuvenation System device was used on facial skin. Measurements of skin hydration, transepidermal water loss (TEWL), melanin and erythema index, temperature, and pH, at baseline and after radiofrequency therapy were performed with the Courage + Khazaka MPA-9 device. Immunohistochemistry on paraffin-embedded sections was used to evaluate the intensity of CD34 expression.Results: Radiofrequency treatment significantly improved facial skin hydration (p < 0.0001). Enhancement of the epidermal barrier observed, by reduced TEWL as a result of a series of treatments with radiofrequency on the facial skin (p < 0.0001), was observed. CD34 was more abundantly expressed after radiofrequency treatment. No side effects were observed.Conclusion: Treatment with radiofrequency is an effective and non-invasive method of facial skin rejuvenation in older women with t2DM, with a relatively short post-procedure recovery time and low potential for severe adverse effects.Keywords: diabetes, skin, radiofrequency, metformin